The Impact Of Social Intelligence On Academic Achievement Of Students Studying Media - Tanakıncı, Orhan; Yıldırım, Osman (Int Scientific Conference Sgem, 14, Kilment Ohridsky Blvd, Sofia, 1797, Bulgaria, 2010)
The importance of understanding Social Intelligence (SI) skills has gravitated form the business management to training activities. Social intelligence skills that students have affect the academic performance of the students. This study aimed at exploring the relationship between one of those well-known concepts, job satisfaction, and emotional intelligence. To this end, a research has been conducted on the students who are attending at school of vocational studies (n=150) of a private university in Istanbul. In the research, RSA-scale (Hjemdal, Friborg, Martinussen, and Rosenvinge) was used to assess students' social intelligence. According to the results, a weak relationship (r<0,40) was revealed between social intelligence and academic achievement. On the other hand, one of the five dimensions of social intelligence was found to be strongly related (r>0,40) to the academic achievement.
Keywords: Social intelligence; Effectiveness; Academic achievement; sosyal zeka; etki; akademik başarı